Ασύρματα δίκτυα αισθητήρων - Δημητρίου, Δημήτρης; Ευαγγέλου, Αντρέας; Χριστοφή, Μιχάλης (Τμήμα Ηλεκτρολόγων Μηχανικών και Μηχανικών Ηλεκτρονικών Υπολογιστών και Πληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
This capstone design work is aimed to build a wireless sensor network for monitoring the temperature at various interiors rooms with wireless communication. This structure consists of three different nodes (terminals) which communicate with a central node (coordinator) that is connected to a personal computer. Each node is autonomous (operates on battery) and comprises a sensor which measures the temperature at regular intervals (i.e.: every 2 hours). These measurements are processed locally by a microprocessor which transmits the results via wireless communication to the central node. The central node receives the data sent by the three other nodes using the 802.15 wireless communication protocol and then imports them to the computer via USB. This program is based on MATLAB and allows the user to present data from each node separately, all together, or the average temperature from all/the selected nodes. With this structure, an individual could easily monitor the indoor temperature of large buildings or the temperature changes. In the future the system could estimate the most suitable location for the central thermostat. The latter is believed to be a good tool for engineers who install central heating/air-conditioning systems.
Keywords: Wireless Sensor Network; Indoor Temperature; Ασύρματο Δίκτυο Αισθητήρων; Θερμοκρασία Εσωτερικού Χώρου